The comparison of long-term results of stress urinary incontinence treatment using Burch operation, TVT and TVT-O procedures based on subjective assessment by operated women - Szyłło, Krzysztof; Bartodziej, Urszula; Włodarczyk, Bogumił; Dobrowolski, Zbigniew; Brucka, Aleksandra (Menopause Review/Przegląd Menopauzalny, 2006)
The aim of the study: to compare long-term results of TVT and TVT-O operations performed among women suffering from stress urinary incontinence. Assessment of the results was based on subjective evaluation by women subjected to operation procedure. Material and methods: We examined 82 patients operated on because of suffered stress urinary incontinence in the Gynaecological Surgery Department, Polish Mother’s Memorial Hospital in Łódź. In the observed population other types of incontinence were excluded before treatment. 32 women were subjected to Burch procedure, in 28 cases TVT operation was performed and the remaining 22 patients were treated with TVT-O. The time of the follow-up observation was respectively: among women after Burch procedure, 1-4 years; after TVT, 6 months to 4 years; after TVT-O, 6-15 months. The results of performed treatment were analysed based on a questionnaire supplied to patients. Results: In the group of women subjected to Burch procedure we obtained by post 19 completed questionnaires out of 32 sent; from patients after TVT 18 questionnaires out of 28 were returned; and we got back 18 out of 22 sent to patients after TVT-O. Incidents of incontinence were frequent in 21.1% cases after Burch operation, in 11.1% of women after TVT, and were not observed in the population with performed TVT-O procedure. The necessity of use of sanitary towels was stated by 41.2% of women who underwent Burch operation. The frequency of passing urine was definitely lower in 55.5% of respondents after TVT-O. 72.2% of women who underwent TVT or TVT-O operation described their comfort of living as definitely better than before the procedure. Conclusions: The lowest occurrence of incontinence episodes was detected among patients subjected to TVT or TVT-O operation, who also described their comfort of living as the most satisfactory.